2019
DOI: 10.1088/1367-2630/ab31cc
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of optical nanofiber interferometer and resonator for the visible range

Abstract: We report the fabrication and characterization of photonic structures using tapered optical nanofibers. Thanks to the extension of the evanescent electromagnetic field outside of the nanofiber two types of devices can be built: a ring interferometer and a knot resonator. We propose a general approach to predict the properties of these structures using the linear coupling theory. In addition, we describe a new source of birefringence due to the ovalization of a nanofiber under strong bending, known in mechanica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Coupled waveguides play an important role in numerous optical devices such as multicore fibers, optical directional couplers, polarization splitters, ring resonators, and interferometers [22][23][24]. Recently, optical devices comprising of twisted or knotted nanofibers have been fabricated [25]. Coupling between two nanofibers has been studied [25,26] in the framework of the coupled mode theory [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coupled waveguides play an important role in numerous optical devices such as multicore fibers, optical directional couplers, polarization splitters, ring resonators, and interferometers [22][23][24]. Recently, optical devices comprising of twisted or knotted nanofibers have been fabricated [25]. Coupling between two nanofibers has been studied [25,26] in the framework of the coupled mode theory [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, optical devices comprising of twisted or knotted nanofibers have been fabricated [25]. Coupling between two nanofibers has been studied [25,26] in the framework of the coupled mode theory [22][23][24]. It has been shown that the guided normal (array) modes of two coupled dielectric rods can be calculated by using the circular harmonics expansion [27].…”
Section: Introductionmentioning
confidence: 99%
“…Sensing using optical methods has been an active field of research in recent years [1][2][3], due to the inherently superior capabilities offered by complex photonic structures [4,5]. Specifically, microstructures incorporated within optical fiber tapers transmitting near-infrared (NIR) light have found comprehensive applications in a variety of sensing scenarios, including in liquid [6][7][8][9], gas [10,11], and other physical [12][13][14][15][16] and chemical [17,18] media.…”
Section: Introductionmentioning
confidence: 99%
“…The optical nanofiber is an air-cladding guiding system with subwavelength diameter, which allows light to be transmitted outside the fiber in the form of evanescent field. In the recent years, the optical properties of nanofibers have been widely used for atomic fluorescence investigation [14], atom trapping [15,16], quantum optics and quantum information [17], chiral quantum optics [18], and optical resonators [19].…”
Section: Introductionmentioning
confidence: 99%